Technology Optimization in Retail: The Effect of Cashless Payment and Inventory Automation on Customer Satisfaction - Aurora, Zahra Lutfia; Amalia, Riska (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the influence of cashless payments and inventory automation on customer satisfaction, both partially and simultaneously. The study used a descriptive quantitative approach with primary data obtained through the distribution of online questionnaires to 100 respondents selected using a purposive sampling technique. Data analysis was conducted using SmartPLS version 4 software. The results showed that cashless payments and inventory automation have a positive and significant effect on customer satisfaction, both partially and simultaneously. These findings indicate that the application of technology in payment systems and inventory management can improve service quality and customer experience. This study concludes that technology optimization in the retail sector plays a significant role in improving customer satisfaction. The implication of this study is the need to develop technology-based service innovations to support service quality and operational efficiency.